Collaborative Governance in Empowering Micro, Small, and Medium Enterprises through SiBakul Jogja Free-Ongkir during Covid-19 - Adella Intan Pertiwi; Awang Darumurti (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2021)
The SiBakul Jogja Free-Ongkir is an empowerment program to helping MSMEs in the province of Yogyakarta affected by the Covid-19. Collaborative governance in the SiBakul Jogja free-ongkir program involves several stakeholders namely, the Department of Cooperatives and SMEs of the Special Region of Yogyakarta, the Java Parama Niaga (JPN) Cooperative, Gojek Jogja, Grab Jogja, and MSMEs affected by Covid-19. In addition, to create collaborative governance, the stakeholders pay attention to three sides to see the efforts to empower the community, namely enabling, empowering, and protecting. The results showed that the collaboration between stakeholders in the SiBakul Jogja Free-Ongkir program was successful. The continuation of the cooperation in empowering MSMEs in the SiBakul Jogja Free-Ongkir program is influenced by various factors, supporting factors, and inhibiting factors. Supporting factors such as a good network structure involving actors who are competent in their fields, adequate sources of funds, and authorities who are in accordance with procedures. The SiBakul Jogja Free-Ongkir program has better changes than before, from manual into an application. The stakeholders made innovations through evaluation results and coordination among them. They were creating the applications namely, Selly, Jagoan SiBakul, and GrabMart. Furthermore, the inhibiting factors are the lack of evaluation by the private sector and lack of technical resources. They need to conduct an even evaluation of stakeholders through good coordination and communication, especially with the JPN Cooperative, increase technical resources, and hold good socialization in presenting the latest innovations from Grab Jogja.